Immigration control and constitutional rights in the chilean constitution: Some considerations for the constitution-making process Control migratorio y derechos fundamentales en la Constitución chilena: Algunas consideraciones para el proceso constituyente - Mayorga Mc Donald, Ramon Victor (My University, 2021)
Despite the absence of explicit references to immigration, constitutional doctrine and case law have considered that the Constitution of 1980 has offered to migrants a rigorous standard of protection of their fundamental rights. This work claims that a future Constitution must preserve this generous constitutional framework, and incorporate norms that direct State towards the adoption of migration policies that focus on the rights and integration of immigrants.
Keywords: constituent process; constitutional immigration law; fundamental rights of immigrants; immigration control